Sincronização do estro e da ovulação em novilhas girolandas: comparação entre os protocolos hormonais ”cidr-b” e “ovsynch - Costa, Antônio Nélson Lima da (2006)
Two oestrus and ovulation synchronization protocols (CIDR-B and OVSYNCH) were tested on 90 acyclical Girolanda heifers. The animals were distributed in three groups. Group I (n=30) was submitted to the OVSYNCH protocol, consisting of: intramuscular (IM) application of 1.0 ml gonadotropin-releasing hormone (GnRH), 2.0 ml rostaglandin F2a (PGF2a) after 7 days, 1.0ml GnRH 48h later, then timed artificial insemination (TAI) 16h after the second application of GnRH. Group II (n=30) was submitted to the CIDR-B protocol, consisting of: introduction of intravaginal CIDR-B implant and application of 2.0 ml estradiol benzoate (EB) IM, implant removal after 8 days, application of 500 UI pregnant mare serum gonadotropin (PMSG) and 2.0 ml PGF2a, a second IM application of BE 24h subsequently, then TAI 30h later (i.e. 54h following implant removal). Group III (n=30; control group) received no hormonal treatment. Gestation was verified ltrasonographically 35 days after the first, second and third AI. The cost-benefit ratio of each protocol was also determined: The CIDR-B protocol was most efficient in the first AI in which it was comparable to the control group in providing a near-natural oestrus quality (conception and pregnancy rates of 60% and 50%, respectively; p<0.05). In the second AI, the two treatments yielded similar pregnancy rates, but differed in conception rates (96% for CIDR-B; 76% for OVSYNCH). Thus the CIDR-B protocol was the more efficient in inducing puberty in Girolanda heifers, featuring the best conception and pregnancy rates in the first AI and considerably reducing age at first birth. It is moreover economically feasible as the implant may be reused provided apropriate care is given to hygiene and handling.